Analysis of the first triad of interacting states (0 2 0), (1 0 0), and (0 0 1) of D216O from hot emission spectra - Mikhailenko S. N. Semen Nikolaevich; Mellau G. Ch.; Starikova E. N.; Tashkun S. A.; Tyuterev Vl. G. (2005, 2005)
Title screen